A sensitive WST-8-based bioassay for PEGylated granulocyte colony stimulating factor using the NFS-60 cell line. (25th November 2014) - Tiwari, Krishna; Wavdhane, Madan; Haque, Shafiul; Govender, Thavendran; Kruger, Hendrik G.; Mishra, Maheshwari K.; Chandra, Ramesh; Tiwari, Dileep
Abstract: Context : Granulocyte colony stimulating factor (G-CSF) has been commonly used to treat neutropenia caused by chemotherapy, radiotherapy, and organ transplants. Improved in vitro efficacy of G-CSF has already been observed by conjugating it to polyethylene glycol (PEG). Objective : The in vivo bioassay using tetrazolium dye with the NFS-60 cell line has been recommended for G-CSF but no such monographs are available for PEGylated G-CSF in pharmacopeias. In the present study, the assay recommended for G-CSF was evaluated for its suitability to PEGylated G-CSF. Materials and methods : The generally used MTS [3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium]-based assay was compared with a bioassay employing a water-soluble tetrazolium dye, WST-8 [2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2, 4-disulfophenyl)-2H-tetrazolium], using NFS-60 cells at a concentration of 7 × 10 5 cells/ml against 800 IU/ml of PEGylated G-CSF at 24, 48, 72, and 72 h time points to determine the efficacy of PEGylated G-CSF. Further, the optimized WST-8 dye-based assay was used to test the potency of various commercially available PEGylated G-CSF preparations. Results : The results demonstrated enhanced sensitivity of the WST-8-based assay over the conventional MTS-based assay for determining the potency of PEGylated G-CSF using the NFS-60 cell line. Conclusion : Our study demonstrates the potential application of WST-8-based bioassays for other biotherapeutic proteins of human and veterinary interest.